The eusocial non-code: Unveiling the impact of noncoding RNAs on Hymenoptera eusocial evolution - Egor Lebedev; Daniil Smutin; Pavel Timkin; Danil Kotelnikov; Amir Taldaev; Nick Panushev; Leonid Adonin (Non-coding RNA Research)
Eusociality, characterized by reproductive division of labor, cooperative brood care, and multi-generational cohabitation, represents a pinnacle of complex social evolution, most notably manifested within the Hymenoptera order including bees, ants, and wasps. The molecular underpinnings underlying these sophisticated social structures remain an enigma, with noncoding RNAs (ncRNAs) emerging as crucial regulatory players. This article delves into the roles of ncRNAs in exerting epigenetic control during the development and maintenance of Hymenopteran eusociality. We consolidate current findings on various classes of ncRNAs, underscoring their influence on gene expression regulation pertinent to caste differentiation, developmental plasticity, and behavioral modulation. Evidence is explored supporting the hypothesis that ncRNAs contribute to epigenetic landscapes fostering eusocial traits through genomic regulation. They are likely to play an important role in eusociality “point of no return”. Critical analysis is provided on the functional insights garnered from ncRNA profiles correlated with caste-specific phenotypes, specifical for phylogenetic branches and transitional sociality models, drawing from comparative genomics and transcriptomics studies. Overall, ncRNA provides a missed understanding of both “genetic toolkit” and “unique genes” hypotheses of eusociality development. Moreover, it points to gaps in current knowledge, advocating for integrative approaches combining genomics, proteomics, and epigenetics to decipher the complexity of eusociality. Understanding the ncRNA contributions offers not only a window into the molecular intricacies of Hymenoptera sociality but also extends our comprehension of how complex biological systems evolve and function.